Making seawalls multifunctional: The positive effects of seeded bivalves and habitat structure on species diversity and filtration rates. (March 2021) - Vozzo, M.L.; Mayer-Pinto, M.; Bishop, M.J.; Cumbo, V.R.; Bugnot, A.B.; Dafforn, K.A.; Johnston, E.L.; Steinberg, P.D.; Strain, E.M.A.
Abstract: The marine environment is being increasingly modified by the construction of artificial structures, the impacts of which may be mitigated through eco-engineering. To date, eco-engineering has predominantly aimed to increase biodiversity, but enhancing other ecological functions is arguably of equal importance for artificial structures. Here, we manipulated complexity through habitat structure (flat, and 2.5 cm, 5 cm deep vertical and 5 cm deep horizontal crevices) and seeding with the native oyster ( Saccostrea glomerata, unseeded and seeded) on concrete tiles (0.25 m × 0.25 m) affixed to seawalls to investigate whether complexity (both orientation and depth of crevices) influences particle removal rates by suspension feeders and colonisation by different functional groups, and whether there are any ecological trade-offs between these functions. After 12 months, complex seeded tiles generally supported a greater abundance of suspension feeding taxa and had higher particle removal rates than flat tiles or unseeded tiles. The richness and diversity of taxa also increased with complexity. The effect of seeding was, however, generally weaker on tiles with complex habitat structure. However, the orientation of habitat complexity and the depth of the crevices did not influence particle removal rates or colonising taxa. Colonisation by non-native taxa was low compared to total taxa richness. We did not detect negative ecological trade-offs between increased particle removal rates and diversity and abundance of key functional groups. Our results suggest that the addition of complexity to marine artificial structures could potentially be used to enhance both biodiversity and particle removal rates. Consequently, complexity should be incorporated into future eco-engineering projects to provide a range of ecological functions in urbanised estuaries. Highlights: Eco-engineering of seawalls often focuses on enhancement of biodiversity. We manipulated seawall complexity to enhance other ecological functions. Increased habitat structure and bivalve seeding enhanced particle removal rates. Habitat structure did not facilitate non-native over native species. Multifunctional eco-engineering is possible without negative ecological trade-offs.